Comparative Analysis Of Energy Expenditure Assessments From The Graded Exercise Test Vs. Galaxy Watch And Apple Watch In Korean College Students During A 30-minute Workout: A Pilot Study - In-Young Oh; Ji-Joon Jeon; Jin-Beom Kim; Jin-Yeong Hyeon; Je-Min Yeon; Hyun-Jun Ha; Seong-Min Han; Dong-Geon Kang; Wi-Young So (Asian Society of Kinesiology, 2024)
OBJECTIVES In the modern era, there is heightened interest in understanding energy expenditure during exercise. Consequently, wearable devices such as the Galaxy Watch and Apple Watch have emerged as pivotal tools for daily health monitoring, given their convenience and increasing popularity. This study aimed to compare the calculated energy expenditure derived from the graded exercise test with readings from Galaxy and Apple Watches during a 30-min exercise session among Korean university students. Through this, we anticipate offering both motivation and clear insights into energy expenditure, thereby potentially aiding in weight management strategies for contemporary individuals. METHODS This study involved 27 college students from Korea National University of Transportation in Chungcheongbuk-do, Korea. We utilized COSMED's exercise load respiratory gas analysis system (Quark-CPET, COSMED, Rome, Italy), along with the Galaxy Watch (Galaxy Watch 5, Samsung, Seoul, Korea) and the Apple Watch (Apple watch series 5, Apple, Cupertino, USA) for measurements. Energy expenditure was monitored in real-time every 5 min throughout the 30-min exercise session. For statistical evaluations, we employed a one-way analysis of variance. Subsequent post-tests utilized the Tukey post-hoc test and Pearson correlation, with a significance level set at p<0.05. RESULTS Initially, no statistically significant difference emerged between energy expenditure readings from the graded exercise test and those from the Galaxy Watch across all time intervals: 5, 10, 15, 20, 25, and 30 min (p>0.05). Conversely, a notable difference was observed when comparing energy expenditure data from the graded exercise test to that of the Apple Watch for time intervals of 10, 15, 20, 25, and 30 min (p>0.05), although the 5-min interval did not exhibit a significant difference (p>0.05). Furthermore, a robust positive correlation was evident between the energy expenditure values derived from the graded exercise test and those from both the Galaxy Watch (r=0.952, p<0.001) and the Apple Watch (r=0.917, p<0.001). CONCLUSIONS Both devices demonstrated high reliability in calculating energy expenditure. Notably, the Galaxy Watch exhibited a more precise calculation compared to the Apple Watch, with a relative reliability margin of 3.5% higher. For individuals, especially those struggling with obesity, precise wearable devices that accurately reflect energy consumption can significantly boost motivation for exercise. Consequently, this study lays a foundation for future advancements in energy expenditure measurement tools, emphasizing enhanced convenience, reliability, and mobility.